YARMOUK UNIVERSITY EFL UNDERGRADUATE STUDENTS’ ENGAGEMENT WITH E-LEARNING TOOLS IN LEARNING THE ENGLISH LANGUAGE - Bassam Al Aroud; Kamariah Yunus; Hamzah Faleh Migdadi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to investigate English as a foreign language students’ engagement in using e-learning tools in learning English language. A mixed method approach was employed comprising 30 students who study English language and literature at Yarmouk University, Jordan in their first year (16 males and 14 females). The respondents of the study were selected randomly, and all of them were selected from the department of English language and literature of Yarmouk University, Jordan. The instrument of the study was a survey questionnaire consisting of 24 items. The data were analyzed using SPSS. The findings of the study have documented that e-learning tools entail a great degree of flexibility and variability, visual knowledge compared to conventional teaching materials and lectures, which are most often unsatisfactory and might not relate to EFL learning. 87% of the respondents revealed that using e-learning tools (MOOCs) affected their language skills’ development positively. In addition, the findings indicated that 90% of the respondents pointed out that these e-learning tools /MOOCs assist language learners and make language-learning fun and meaningful. The findings of this study revealed that the foremost factors affecting EFL students’ approval and use of e-learning tools were facilitating conditions, social influence, effort expectancy and performance expectancy. Such findings revealed the significance of e-learning tools from the point of view of this mixed-method research. The findings indicated that past experiences relevant influenced EFL Jordanian undergraduate students at Yarmouk University use of e-learning tools / MOOCs when learning English language.